If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -5x = 15 + -4x Solving 20 + -5x = 15 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 20 + -5x + 4x = 15 + -4x + 4x Combine like terms: -5x + 4x = -1x 20 + -1x = 15 + -4x + 4x Combine like terms: -4x + 4x = 0 20 + -1x = 15 + 0 20 + -1x = 15 Add '-20' to each side of the equation. 20 + -20 + -1x = 15 + -20 Combine like terms: 20 + -20 = 0 0 + -1x = 15 + -20 -1x = 15 + -20 Combine like terms: 15 + -20 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 15+7.50m=75 | | 8=2w-16 | | 7x-9x=28 | | 442.30=210+1.01x | | 3x-63=x-37 | | 2x^2-45x+100=0 | | 0-2y+10=0 | | 3x^2-14-24=0 | | 3x+18=48x | | 7x+7=80 | | 8x+14=5x-47 | | 4p-5t+3= | | 3j-1=5 | | 36+4-8-x=25 | | 36+4-8-x=25 | | 4p-5t+3= | | 36+4-8-x=25 | | 10=r^9 | | -1-2y+10=0 | | V^2-10r+24=0 | | 2=c-1 | | 10(x-1)-5[2x-3(x-1)]=2(10x-11) | | 3s+7.67=14.57 | | 7x^2+6x-1=-1 | | 6b(2-10)=65(N+160) | | 1+y=18 | | 37=3(10x-5)+2(3x-10) | | 3x+2(2x-5)=4 | | Y=1(13)+2 | | 67=9x+4 | | x-11=9+3x | | 3x+5=-8(6+5x) |